Abnormal cardiac axis as a prenatal marker of left pulmonary artery sling. Issue 2 (26th November 2015) - Ishii, Yoichiro; Miyamoto, Takashi; Nakajima, Kimiko; Tanaka, Kensuke; Ikeda, Kentaro; Inamura, Noboru; Takagi, Takeshi; Kobayashi, Tomio; Arakawa, Hirokazu
Abstract: Left pulmonary artery sling (LPAS) is a rare vascular anomaly. The left pulmonary artery arises distally from the right pulmonary artery on the right side of the trachea and passes between the trachea and esophagus towards the left lung, compressing the lower trachea. LPAS is associated with congenital tracheal stenosis, which frequently requires early surgical intervention and has a poor prognosis due to severe airway obstruction after birth. Therefore, LPAS should be prenatally diagnosed to prepare for surgical intervention for tracheal stenosis. To the best of our knowledge, there are few reports on prenatal echocardiographic findings in LPAS. We report three prenatal cases of LPAS, which resulted in respiratory symptoms. We discuss fetal ultrasound findings and highlight the abnormal rotation of the fetal cardiac axis to the right as a useful sign in the prenatal screening of LPAS.